Banking globalization, local lending, and labor market effects: Micro-level evidence from Brazil - Felix Noth; Matias Ossandon Busch (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
This paper estimates the effect of a foreign funding shock to banks in Brazil after the collapse of Lehman Brothers in September 2008. Our robust results show that bank-specic shocks to Brazilian parent banks negatively affected lending by their individual branches and trigger real economic consequences in Brazilian municipalities: More affected regions face restrictions in aggregated credit and show weaker labor market performance in the aftermath which documents the transmission mechanism of the global financial crisis to local labor markets in emerging countries. The results represent relevant information for regulators concerned with the real effects of cross-border liquidity shocks.
URN:NBN:fi:bof-201706141354
Keywords: E24; E44; G01; G21; 330